Ligand-based poly(phenylenediamine) adsorbents for enhanced removal of phosphate from water - Mdlalose, Lindani; Balogun, Mohammed; Setshedi, Katlego; Klavins, Maris; Chimuka, Luke; Chetty, Avashnee (Polymer bulletin (Berlin, Germany), 2022)
Phosphorus removal from effluents is vital to avoid eutrophication. The subject study presents the development and performance of poly(phenylenediamine) isometric adsorbents produced through oxidation using (NH 4 ) 2 S 2 O 8 and K 2 Cr 2 O 7 oxidants. K 2 Cr 2 O 7 synthesized polymers showed better adsorption capacities. The presence of Cr Lewis acid on the surface endorsed phosphate interaction through inner-sphere complex mechanism. The maximum adsorption capacities for K 2 Cr 2 O 7 synthesized polymers were 143, 217 and 69.0 mg/L for poly( o -phenylenediamine), poly( m -phenylenediamine) and poly( p -phenylenediamine) adsorbents, respectively. The superior performance of poly( m -phenylenediamine) was associated with minimal symmetrical arrangement, hence it was more amorphous as indicated by XRD patterns. Kinetic model fitted pseudo-second-order and isotherm favoured Langmuir. Adsorption process was also controlled by pore diffusion and external mass transfer in the sorbent. Poly( m -phenylenediamine) displayed high affinity in the presence of competing anions and was amenable to recycling.